2006
DOI: 10.1002/asia.200600338
|View full text |Cite
|
Sign up to set email alerts
|

Columnar Mesophase Formation of Cyclohexa‐m‐phenylene‐Based Macrocycles

Abstract: Two novel discotic macrocycles, substituted cyclohexa-m-phenylene (CHP) and cyclo-3,6-trisphenanthrylene (CTP), and the linear oligomer 3,3':6',3''-terphenanthrene (TP) as a model substance have been synthesized by repetitive cross-coupling reactions. To correlate the molecular design with the supramolecular architecture and the established macroscopic order, 2D wide-angle X-ray scattering experiments were performed on mechanically extruded filaments. At room temperature in their crystalline phases, all three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 35 publications
2
51
0
2
Order By: Relevance
“…The prerequisite for a smoothly occurring cyclotrimerization is a 120° substitution pattern on the molecular building block, as reflected by our previous investigations 21–25. Thus, a five‐step synthetic route from parent 1,10‐phenanthroline ( 1 ) to the target 2,9‐dichloro‐5,6‐dialkoxy‐1,10‐phenanthroline precursors 6 a – c was developed (Scheme ).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The prerequisite for a smoothly occurring cyclotrimerization is a 120° substitution pattern on the molecular building block, as reflected by our previous investigations 21–25. Thus, a five‐step synthetic route from parent 1,10‐phenanthroline ( 1 ) to the target 2,9‐dichloro‐5,6‐dialkoxy‐1,10‐phenanthroline precursors 6 a – c was developed (Scheme ).…”
Section: Resultsmentioning
confidence: 73%
“…For the cyclotrimerization of precursors 6 a – c towards macrocycles 7 a – c , a standard Yamomoto protocol2123, 35, 36 was carried out in an overall 3/1 mixture of toluene/DMF at 60 °C under pseudo‐dilution conditions (cf. Scheme , for the proposed reaction pathway towards 7 a – c , see Scheme S2 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The software WSXM was used to analyse the STM images. 39 The DFT calculations were performed using the CP2K package (CP2K version 2.3.43; CP2K is freely available in http://www.cp2k.org/) with the mixed Gaussian and plane wave formalism 40 and periodic boundary conditions. The exchange and correlation functional used was the revised 41 version of the Perdew-Burke-Ernzerhof (PBE) 42 function.…”
Section: Methodsmentioning
confidence: 99%
“…In the course of our studies of anthracene–acetylene oligomers, we found that bulky mesityl (Mes) groups on an anthracene unit reasonably improved the solubility and stability because those groups protected the aromatic cores from intermolecular stacking and undesired reactions . These findings inspired us to synthesize [6]CANT*, a [6]CANT analogue having twelve Mes groups at all 9,10‐positions, as a novel cycloarylene consisting of large polycyclic aromatic hydrocarbon (PAH) units . We herein report the synthesis, structure, spectroscopic properties, and unique dynamic process of [6]CANT* as the first [6]CANT derivative, as well as the synthesis of related linear oligomers, [ n ]ANT* derivatives, as new oligoanthrylenes .…”
Section: Figurementioning
confidence: 99%